Tick-borne Relapsing Fever and Borrelia hermsii, Los Angeles County, California, USA - Schwan, Tom G. (Centers for Disease Control and Prevention, 2009)
The primary cause of tick-borne relapsing fever in western North America is Borrelia hermsii, a rodent-associated spirochete transmitted by the fast-feeding soft tick Ornithodoros hermsi. We describe a patient who had an illness consistent with relapsing fever after exposure in the mountains near Los Angeles, California, USA. The patient’s convalescent-phase serum was seropositive for B. hermsii but negative for several other vector-borne bacterial pathogens. Investigations at the exposure site showed the presence of O. hermsi ticks infected with B. hermsii and the presence of rodents that were seropositive for the spirochete. We determined that this tick-borne disease is endemic to the San Gabriel Mountains near the greater Los Angeles metropolitan area.